(untitled) (Journal of Human Sciences, 2021)
The educational curriculum on which the noble Companions and those who followed them were brought up is the Holy Book of God revealed to our Messenger [may God’s prayers and peace be upon him], which made it strike a proper balance between work in this world and the hereafter. The other, and when the defect occurred after that on the part of some Muslims in the understanding and application of Islam, there has become a kind of exaggeration or estrangement in the eyes of some Muslims towards those who multiply certain types of worship, as they have become the object of appreciation and reverence from some And if they do not show interest in the types of worship in Islamic jurisprudence because it is the immunity that protects politics from deviation; Because it is education in the first place, participating in its abolition is considered a contribution to the destruction of other individuals and societies, such as jihad in the way of God Almighty and enjoining what is good. And the prohibition of evil and benevolence to Muslims, so that society runs in one context, to reform the individual and the family system in most educational institutions and others, based on the approach of the jurists and those who followed them until the Day of Judgment, and the study reached the following 1- The most important foundations upon which the human personality is built through the curriculum of education is the Noble Qur’an and the Sunnah of the Prophet, upon whom is the best prayer and the most complete submission.